1999
DOI: 10.1098/rstb.1999.0470
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography in the study of human somatosensory cortical processing

Abstract: Magnetoencephalography (MEG) is a totally non-invasive research method which provides information about cortical dynamics on a millisecond time-scale. Whole-scalp magnetic field patterns following stimulation of different peripheral nerves indicate activation of an extensive cortical network. At the SI cortex, the responses reflect mainly the activity of area 3b, with clearly somatotopical representations of different body parts. The SII cortex is activated bilaterally and it also receives, besides tactile inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
184
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(221 citation statements)
references
References 98 publications
35
184
0
2
Order By: Relevance
“…These results replicate the well-known spatiotemporal patterns of responses to painful [Kakigi et al, 2005] and tactile [Hari and Forss, 1999] stimuli and provide an elementary neural network subserving simple reaction times to painful and tactile stimuli.…”
Section: Resultssupporting
confidence: 73%
“…These results replicate the well-known spatiotemporal patterns of responses to painful [Kakigi et al, 2005] and tactile [Hari and Forss, 1999] stimuli and provide an elementary neural network subserving simple reaction times to painful and tactile stimuli.…”
Section: Resultssupporting
confidence: 73%
“…MEG provides an excellent temporal resolution, orders of magnitude better than in other methods for measuring cerebral activity, as magnetic resonance imaging, single-photon-emission computed tomography and positron-emission tomography [1]. A reasonable spatial resolution on the scalp can also be achieved, although it drastically depends on the source configuration [2]. In addition, magnetic fields are not distorted by the resistive properties of the skull [1].…”
Section: Introductionmentioning
confidence: 93%
“…This may be due to the relatively large number of neuronal sources activated in a relatively short period of time by the median-nerve stimulation with typical repetition rates, which challenges covariance-based analysis techniques such as beamformer. For example, previous neurophysiology studies (including MEG) have shown that strong stimulation of the peripheral nerve can activate: 1) contralateral primary somatosensory area (SI) with a first component around 20 ms post-stimulus in humans (Wood et al 1985;Hari et al 1993;Forss et al 1994;Kawamura et al 1996;Mauguiere et al 1997a;Mauguiere et al 1997b;Forss and Jousmaki 1998;Jousmaki and Forss 1998;Hari and Forss 1999;Huang et al 2000); 2) contralateral primary motor area (MI) with a first component around 20-30 ms post-stimulus in humans (Rosen and Asanuma 1972;Lemon and Porter 1976;Jones et al 1978Jones et al , 1979Wong et al 1978;Lemon van der Burg 1979;Lemon 1981;Davidoff 1990;Baldissera and Leocani 1995;Kawamura et al 1996;Spiegel et al 1999;Huang et al 2000); 3) contralateral superior parietal area (Jones et al 1978(Jones et al , 1979Forss et al 1994;Boakye et al 2000;McGlone et al 2002;Waberski et al 2002); 4) supplementary motor area (SMA) (Urbano et al 1997;Boakye et al 2000;Barba et al 2001); 5) premotor area (Park and Del Toro 1995;Mauguiere et al 1997b;Bergeron and Braddom 1998); and 6) bilateral secondary somatosensory areas (SII) …”
Section: Introductionmentioning
confidence: 99%